P272 The importance of directly observed therapy in perinatal tuberculosis. (6th June 2017) - Yahşi, Aysun; Erat, Tuğba; Özdemir, Halil; Kara, Tuğçe Tural; Altun, Ekin Zeynep; Kocabaş, Bilge Aldemir; Ince, Erdal; Çiftçi, Ergin
Abstract : 9.5 month-old boy presented with a one-month history of cough and lymphadenopathy. The mother was diagnosed with pulmonary tuberculosis when the baby was 1, 5 months old. Thus, the breastfeeding was stopped and isoniazid prophylactic therapy was recommended to baby. However, the treatment was only applied between 6–9 months old by the family. He was evaluated for pneumonia at first and nonspecific antibiotic therapies were started. After ten-day treatment, the symptoms didn't get better. He was again evaluated and three serial samples of gastric aspirates that sent for ARB and Tbc PCRes were positive. Chest CT revealed that concerning the whole middle and lower lobes in the right lung at the widespread consolidation area, necrotic areas where the largest reached over 23 × 13 mm was monitored. He was administered a four-drug anti-tuberculous treatment of INH (11.5 mg/kg), rifampicin (15 mg/kg), pyrazinamide (25 mg/kg), etambuthol (18.75 mg/kg). At the first month of treatment all acid fast stains and PCR were negative. Even though ChestCT were the same, findings showed remarkable improvement After 2 months the child was discharged to his home with two-drug- maintence therapy. As well as early diagnosis and treatment, directly observed therapy is crucial in tuberculosis.